(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The removal of petroleum subsidies in Nigeria has sparked considerable debate, with proponents highlighting potential economic gains and critics warning of adverse effects on key economic indicators. This study aims to assess the impact of subsidy removal on major macroeconomic variables, including inflation, GDP growth, government revenue, and fiscal deficit, using econometric techniques. Time-series data from 2000 to 2024 was analysed through regression models to evaluate the causal relationship between subsidy removal and these economic indicators. The findings reveal a positive and significant relationship between subsidy removal and government revenue, with an increase of approximately 112.45 billion NGN, and a reduction in the fiscal deficit by about 5.23 billion NGN. However, the analysis also indicates an initial inflationary spike of 3.56 percentage points and a short-term contraction in GDP growth. In the long term, GDP growth recovers, driven by more efficient resource allocation. These results offer important insights for policymakers, suggesting that while subsidy removal can foster fiscal consolidation, it must be carefully managed to mitigate short-term negative impacts on inflation and economic growth.